Clinical Characteristics and Risk Factors for Disease Severity and Death in Patients With Coronavirus Disease 2019 in Wuhan, China - Zou, Li; Dai, Lijun; Zhang, Yangyang; Fu, Wenning; Gao, Yan; Zhang, Zhaohui; Zhang, Zhentao (Frontiers in Medicine, 2020)
Objective: To describe the clinical manifestations and outcomes of COVID-19, and explore the risk factors of deterioration and death of the disease. Methods: In this retrospective study, we collected data from 121 COVID-19 cases confirmed by RT-PCR and next-generation sequencing in Renmin Hospital of Wuhan University from January 30, 2019, to March 23, 2020, and conducted statistical analysis. Results: A total of 121 patients were included in our study, the median age was 65 years (IQR, 55.0–71.5 years), and 54.5% cases were men. Among those cases, 52 (43.0%) cases progressed to severe, and 14 (11.6%) died. Overall, the most common manifestations were fever (78.5%) and respiratory symptoms (77.7%), while neurological symptoms were found in only 9.9% of the patients. 70.2% of all the cases had comorbidities, including hypertension (40.5%) and diabetes (20.7%). On admission, cases usually show elevated levels of neutrophils (27.3%), D-dimer (72.6%), Interleukin-6 (35.2%), Interleukin-10 (64.4%), high-sensitivity C-reactive protein (82.6%), and lactate dehydrogenase (62.0%), and decreased levels of lymphocytes (66.9%), CD3 cells (67.2%), and CD4 cells (63.0%). The proportional hazard Cox models showed that the risk factors for severity progression and death included comorbidities (HR: 4.53, 95% CI: 1.78–11.55 and HR: 7.81, 95% CI: 1.02–59.86), leukocytosis (HR: 1.13; 95% CI: 1.05–1.22 and HR: 1.25, 95% CI: 1.10–1.42), neutrophilia (HR: 1.15, 95% CI: 1.07–1.13 and HR: 1.28, 95% CI: 1.13–1.46, and elevated LDH (HR: 1.14, 95% CI: 1.12–1.15 and HR: 1.11, 95% CI: 1.10–1.12). Elevated D-dimer (HR: 1.02, 95% CI: 1.01–1.03), IL-6 (HR: 1.01, 95% CI: 1.00–1.02) and IL-10 levels (HR: 1.04, 95% CI: 1.01–1.07) were also risk factors for the progression of disease severity. Meanwhile, lymphopenia and wake immune responses [e.g., lower CD3, CD4, or CD19 counts (all HR < 1)] were associated with disease deterioration and death. Conclusions: Severe cases and death of COVID-19 are associated with older age, comorbidities, organ dysfunction, lymphopenia, high cytokines, and weak immune responses.